Vulvar Myiasis During Pregnancy - Mauro R. L. Passos; Renata Q. Varella; Rogério R. Tavares; Nero A. Barreto; Cláudio C. C. Santos; Vandira M. S. Pinheiro; Renato S. Bravo; Maurício H. L. Morelhi (Hindawi Limited, 2002)
Myiasis is a parasitic infestation caused by the larvae of several fly species. Diagnosis and treatment are simple. The location of this infestation at the vulvar area is, however, an extremely rare occurrence. The authors present two cases of vulvar myiasis affecting pregnantwomen. The first case is a 19-year-old pregnant girl with vulvar myiasis and concomitant syphilis, vaginal trichomoniasis and genital candidiasis. The patient was also HIV-positive. The second case is a 17-year-old pregnant girl with vulvar myiasis associated with extensive vulvar condyloma acuminatum lesions.